Effect of early lactation foot trimming in lame and non-lame diary heifer: a randomised controlled trial - Maxwell, O.J.R.; Hudson, C.D.; Huxley, J.N. (BMJ Publishing Group, 2015)
Foot trimming is a common management intervention in prevention of lameness in dairy cattle. Despite this, there is surprisingly limited experimental evidence on its efficacy, especially in regard to primiparous heifers. A randomised, negatively controlled trial was conducted to investigate the association between an early lactation foot trim on primiparous animals and production outcomes. 282 heifers were enrolled from eight farms in the UK, and randomly assigned to treatment or control groups. Milk yield (305-day-adjusted whole-milk yield) was not significantly different between groups (trimmed 7727 litres, untrimmed 7646 litres). However, multivariate regression analysis demonstrated that this relationship was confounded by lameness state. Animals that were lame at the time of trimming gave significantly more milk (734 litres, P=0.02) than those that were non-lame and untrimmed. The present results suggest that, based on milk production alone, it would not have been cost beneficial to trim all heifers; however, a targeted intervention aimed at lame animals would have delivered a substantial return on investment. As a very minimum, the authors recommend heifers should be regularly assessed in early lactation, and treated as soon as they are identifiably lame. The high prevalence of lesions identified suggests routine trimming for all heifers may be justifiable on welfare grounds even if the milk-yield benefits are marginal.